Outcome of COVID-19 in patients with idiopathic inflammatory myopathy during the Omicron wave in China: A longitudinal observational study - Ying Li; Xiaolan Tian; Chao Sun; Yangyang Wei; Wei Jiang; Linrong He; Chunjia Li; Lu Zhang; Guochun Wang; Xin Lu (PLoS ONE, 2025)
Objective The coronavirus disease pandemic brought unknown challenges to patients with idiopathic inflammatory myopathy, who are often heavily immunosuppressed and have comorbidities. We aimed to investigate the outcomes and risk factors of coronavirus disease in Chinese patients with idiopathic inflammatory myopathy during the Omicron wave. Methods This observational study included patients with idiopathic inflammatory myopathy who visited the China-Japan Friendship Hospital. Data on baseline characteristics and coronavirus disease-related information were collected through medical records and surveys, and subsequently analysed. Results Overall, 204 patients with idiopathic inflammatory myopathy were identified; dermatomyositis was the most common idiopathic inflammatory myopathy subtype. Data were collected from 185 patients with idiopathic inflammatory myopathy who tested positive for severe acute respiratory syndrome coronavirus 2 via polymerase chain reaction or antigen tests; of these, 20 experienced a severe course of the disease, and 9 died. All patients with severe coronavirus disease had idiopathic inflammatory myopathy-associated interstitial lung disease, and the most common antibodies observed in patients with mortality were anti-aminoacyl tRNA synthetase and anti-MDA-5 antibodies. Furthermore, 45.0% of patients in the severe disease group took > 15.0 mg of prednisone daily before infection, a significantly higher proportion than that in the non-severe disease group. Advanced age, mechanics’ hands, dyspnoea, chronic cough and fever during the course of myositis, low lymphocyte count, low serum albumin level, and high D-dimer and ferritin levels before infection were prominent in patients with severe coronavirus disease. Albumin levels below 35.0 g/L and ferritin levels above 306.8 ng/mL were independent risk factors of severe coronavirus disease. Conclusion Omicron did not worsen the overall outcomes of coronavirus disease for patients with idiopathic inflammatory myopathy; however, specific risk factors were identified, highlighting the need for targeted management strategies.